Intrinsic differences between FVIIIa mimetic bispecific antibodies and FVIII prevent assignment of FVIII‐equivalence. (26th April 2019) - Leksa, Nina C.; Aleman, Maria M.; Goodman, Allison G.; Rabinovich, Deana; Peters, Robert; Salas, Joe
Abstract: Essentials Non‐factor VIII (FVIII) therapies for hemophilia A, such as bispecific antibodies (bsAbs), are in development. Bispecific antibodies are intrinsically different from FVIII and lack many of the same regulatory mechanisms. These differences complicate assignment and interpretation of FVIII‐equivalent activity. Inability to assign FVIII equivalence compromises our capacity to assess hemostatic potential of bsAb therapies. Background: Activated factor VIII (FVIIIa) mimetic bsAbs aim to enable prophylactic treatment of hemophilia A patients with and without inhibitors. With different mechanisms of action, benchmarking their activity against FVIII to determine efficacious yet safe dosage is difficult. Objective: To compare the activities of sequence identical emicizumab (SI‐Emi) and another bsAb, BS‐027125, to recombinant FVIII (rFVIII) using clinical and nonclinical assays and to evaluate our ability to assign a FVIII‐equivalent value to bsAbs and implications thereof. Methods: Activities of SI‐Emi, BS‐027125, and rFVIII were measured by one‐stage clotting assay, chromogenic factor Xa generation assay, and thrombin generation assay. We also assessed the activity of anti‐FIXa and anti‐FX bivalent homodimers of each bsAb and probed the effect of different reagents in thrombin generation assay (TGA). Results: The FVIII‐like activity of SI‐Emi and BS‐027125 ranged greatly across each assay, varying both by parameter measured within an assay and by reagents used. Notably, SI‐Emi anti‐FIXa bivalent homodimer had meaningful activity in several assays, whereas BS‐027125 anti‐FIXa bivalent homodimer only had activity in the chromogenic assay. Surprisingly, SI‐Emi displayed activity in the absence of phospholipids, while BS‐027125 had minimal phospholipid‐independent activity. Conclusions: Bispecific antibodies demonstrate little consistency between assays tested here owing to intrinsic differences between FVIII and bsAbs. While some trends are shared, the bsAbs also differ in mechanism. These inconsistencies complicate assignment of FVIII‐equivalent values to bsAbs. Ultimately, a deeper mechanistic understanding of bsAbs as well as bsAb‐tailored assays are needed to monitor and predict their hemostatic potential and long‐term efficacy and safety confidently.